# Ex 13.2, 11

Last updated at March 9, 2017 by Teachoo

Last updated at March 9, 2017 by Teachoo

Transcript

Ex 13.2, 11 Find the derivative of the following functions: (i) sin x cos x Let f (x) = sin x cos x. Let u = sin x & v = cos x ∴ f(x) = uv So, f’(x) = (uv)’ = u’v + v’u Here, u = sin x So, u’ = cos x & v = cos x So, v’ = – sin x Now, f’(x) = (uv)’ = u’v + v’ u = cos x . cos x + ( – sin x) sin x = cos2x – sin2x = cos 2x Hence f’(x) = cos 2x Ex13.2, 11 Find the derivative of the following functions: (ii) sec x Let f (x) = sec x f(x) = 1 cos𝑥 Let u = 1 & v = cos x So, f(x) = 𝑢𝑣 ∴ f’(x) = 𝑢𝑣′ using quotient rule f’(x)= 𝑢′𝑣 − 𝑣′𝑢 𝑣2 Finding u’ & v’ u = 1 u’ = 0 & v = cos x v’ = – sin x Now, f’(x) = 𝑢𝑣′ = 𝑢′𝑣 − 𝑣′𝑢 𝑣2 = 0( cos𝑥) − (− sin𝑥) (1) 𝑐𝑜𝑠2𝑥 = 0 + sin𝑥 𝑐𝑜𝑠2𝑥 = sin𝑥 𝑐𝑜𝑠2𝑥 = sin𝑥 cos𝑥 . 1 cos𝑥 = tan x . sec x Hence f’(x) = tan x . sec x Ex13.2, 11 Find the derivative of the following functions: (iii) 5 sec x + 4 cos x Let f (x) = 5 sec x + 4 cos x. Now, f’ (x) = ( 5 sec x + 4 cos x)’ = (5 sec x)’ + (4 cos x)’ = 5 (sec x . tan x) + 4 ( – sin x) = 5 sec x . tan x – 4 sin x Ex 13.2, 11 Find the derivative of the following functions: (iv) cosec x Let f (x) = cosec x f(x) = 1 sin𝑥 Let u = 1 & v = sin x ∴ f(x) = 𝑢𝑣 So, f’(x) = 𝑢𝑣′ Using quotient rule f’(x) = 𝑢′𝑣 − 𝑣′𝑢 𝑣2 Finding u’ & v’ u = 1 u’ = 0 & v = sin x v’ = cos x Now, f’(x) = 𝑢𝑣′ = 𝑢′𝑣 − 𝑣′𝑢 𝑣2 = 0 ( sin𝑥) − cos𝑥 (1) 𝑠𝑖𝑛2𝑥 = 0 − 𝑐𝑜𝑠 𝑥 𝑠𝑖𝑛2𝑥 = − 𝑐𝑜𝑠 𝑥 𝑠𝑖𝑛2𝑥 = − 𝑐𝑜𝑠 𝑥 sin𝑥 . 1 sin𝑥 = – cot x cosec x = – cosec x cot x Hence f’(x) = – cosec x cot x Ex13.2, 11 Find the derivative of the following functions: (v) f (x) = 3cot x + 5cosec x. Given f (x) = 3cot x + 5cosec x Now, f’(x) = (3cot x + 5cosec x)’ = 3(cot x)’ + 5( cosec x)’ = – 3cosec2x – 5 cot x cosec x = – 3 cosec2x – 5 cosec x cot x Ex13.2, 11 Find the derivative of the following functions: (vi) f (x) = 5sin x – 6 cos x + 7. Let f (x) = 5sin x – 6cos x + 7 f’(x) = (5 sin x – 6 cos x + 7)’ = (5 sin x)’ – (6 cos x)’ + (7)’ = 5 cos x – 6 ( – sin x ) + 0 = 5 cos x + 6 sin x Ex13.2, 11 Find the derivative of the following functions: (vii) f (x) = 2 tan x – 7 sec x f (x) = 2 tan x – 7 sec x. Now, f’(x) = (2 tan x – 7 sec x)’ = (2tan x)’ – (7sec x)’ = 2 (tan x)’ – 7 (sec x)’ = 2 sec2 x – 7 (sec x tan x) = 2 sec2 x – 7 sec x tan x

Example 2
Important

Example 3 Important

Ex 13.1, 6 Important

Ex 13.1,10 Important

Ex 13.1, 13 Important

Ex 13.1, 16 Important

Ex 13.1, 22 Important

Ex 13.1, 25 Important

Ex 13.1, 28 Important

Ex 13.1, 30 Important

Ex 13.1, 32 Important

Ex 13.2, 9 Important

Ex 13.2, 11 Important You are here

Example 20 Important

Example 21 Important

Example 22 Important

Misc 1 Important

Misc 6 Important

Misc 9 Important

Misc 24 Important

Misc 27 Important

Misc 28 Important

Misc 30 Important

Important Question for exams Class 11

- Chapter 1 Class 11 Sets
- Chapter 2 Class 11 Relations and Functions
- Chapter 3 Class 11 Trigonometric Functions
- Chapter 4 Class 11 Mathematical Induction
- Chapter 5 Class 11 Complex Numbers
- Chapter 6 Class 11 Linear Inequalities
- Chapter 7 Class 11 Permutations and Combinations
- Chapter 8 Class 11 Binomial Theorem
- Chapter 9 Class 11 Sequences and Series
- Chapter 10 Class 11 Straight Lines
- Chapter 11 Class 11 Conic Sections
- Chapter 12 Class 11 Introduction to Three Dimensional Geometry
- Chapter 13 Class 11 Limits and Derivatives
- Chapter 14 Class 11 Mathematical Reasoning
- Chapter 15 Class 11 Statistics
- Chapter 16 Class 11 Probability

About the Author

Davneet Singh

Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He provides courses for Mathematics from Class 9 to 12. You can ask questions here.